Secrets and lies in psychotherapy - Farber, Barry A. (Barry Alan), 1947-; Blanchard, Matt; Love, Melanie (American Psychological Association, 2019)
Using the results of two comprehensive studies involving over 1,000 clients, this book examines the nature of lies and concealment in therapy, and shows therapists how to prevent or minimize client concealment.